Meta Analisis Pengaruh Media E-Learning terhadap Hasil Belajar pada Pendidikan Kejuruan - Yasdinul Huda; Elfi Tasrif; Fadhillah Majid Saragih; Waradzi Mustakim; Nisa Vebriani (Departement of Mathematics Education, 2023)
The goal of this study was to evaluate articles by measuring the value effect size of the impact of e-learning learning media on student learning outcomes. Meta-analysis is the research methodology used in this case. Twenty journal papers will be analyzed for this study depending on the types of students who attend vocational high schools and universities. Based on topics that score 1.81 for SMK student subjects and 1.13 for student subjects who are in the very high category, the study's findings are an examination of the average amount of effect on the usage of e-learning media on student learning outcomes. The average effect size is extremely high in the gnognome-based learning model, according to learning model, with a value of 2.43, which is in the very high category. Based on the findings of the analysis, it can be concluded that the usage of e-learning resources significantly affects students' learning outcomes, both for SMK students and for university students.